PENGARUH KUALITAS PRODUK DAN KESESUAIAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK EMINA - Yeni Yeni; Siti Komariah Hildayanti; Muhammad Bahrul Ulum (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
This study aims to determine the effect of product quality and price suitability on purchasing decisions for Emina products at Guardian in Palembang Square Mall, the sample used was guardian consumers who had the following criteria: consumers of Emina’s products, women who have visited and bought Emina’s products at Guardian Palembang Square, women who are currently still using Emina’s products. Sampling in this study were 85 respondents as a sample. Data collection techniques by distributing questionnaires via Google Form. Based on the results of the t test analysis on the product quality variabel, the probability value (sig) is 0.000 <0.05 and the t count value is 9.045 > t table 1.663, so it can be interpreted that product quality partially affects the decision to purchase Emina products. In the price suitability variabel, it is known that the sig value is 0.000 < 005 and the tcount value is 4.747 > t table 1.663, so it can be concluded that price suitability partially affects the decision to purchase Emina products. The results of the F test analysis obtained an Fcount value of 172,805 > F table 3.96 with a significance of 0.000, it can be concluded that the product quality and price variabels simultaneously have a significant effect on the Purchasing Decision variabel.